Weeds as Potential Inoculum Reservoir for Colletotrichum nymphaeae Causing Strawberry Anthracnose in Iran and Rep-PCR Fingerprinting as Useful Marker to Differentiate C. acutatum Complex on Strawberry - Karimi, Kaivan; Arzanlou, Mahdi; Pertot, Ilaria (Frontiers in Microbiology, 2019)
Strawberry anthracnose caused by Colletotrichum spp. is considered one of the most serious and destructive disease of strawberry worldwide. Weeds, as possible hosts of the pathogen, could have a role as potential inoculum reservoir. To prove this hypothesis, symptomless weeds were collected in strawberry fields showing anthracnose symptoms in Iran. Ten isolates with Colletotrichum-like colonies were recovered from symptomless Amaranthus viridis L., Convolvulus arvensis L., Fumaria officinalis L., Lactuca serriola L. and Sonchus oleraceus L. plants. The isolates were identified as C. nymphaeae, based on a combination of morphological and sequence data of TUB and GADPH genes. This identification was further validated using Rep-PCR fingerprinting analysis, which produces species-specific DNA fingerprints and unveils inter and intra variation of the species examined in this study. Moreover, rep-PCR marker was used to reveal accurate taxonomic position of Colletorichum spp. causing strawberry anthracnose belonging to the C. acutatum complex, including C. acutatum sensu stricto, C. fiorinae, C. godetiae, C. nymphaeae, C. salicis and C. simmondsii. The C. nymphaeae isolates originating from symptomless weeds confirmed their pathogenicity on detached strawberry, proving that weeds in strawberry field may have a role as reservoir of inoculum. However, further studies are necessary to quantify their actual contribution to anthracnose epidemics in strawberry fields.